2022
DOI: 10.1021/acsmacrolett.2c00021
|View full text |Cite
|
Sign up to set email alerts
|

UCST-Type Polymer Capsules Formed by Interfacial Complexation

Abstract: Formation of aqueous-core polymer capsules exhibiting an upper critical solution temperature (UCST) was achieved using surfactant–polymer interfacial complexation in water-in-oil inverse emulsions. In fluorinated oil, Coulombic interactions between Krytox, an anionic oil-soluble surfactant, and a cationic poly­(lysine) grafted with poly­(acrylamide-co-acrylonitrile) enabled the formation of an adsorbed polymer shell at the surface of water droplets. The thermoresponsiveness of the polymer shell was assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…For that, FRAP is undertaken by photobleaching a small fluorescent region within ALP-AOPS. [15,61] Empty AOPS pretreated with precursors are also used as a control. FRAP measurements are carried out after 6 h incubation for both protocell systems, using 0.7 mm precursor.…”
Section: Dynamics and Viscosity Of Artificial Skeleton-based Alp-aops...mentioning
confidence: 99%
“…For that, FRAP is undertaken by photobleaching a small fluorescent region within ALP-AOPS. [15,61] Empty AOPS pretreated with precursors are also used as a control. FRAP measurements are carried out after 6 h incubation for both protocell systems, using 0.7 mm precursor.…”
Section: Dynamics and Viscosity Of Artificial Skeleton-based Alp-aops...mentioning
confidence: 99%
“…Phase separation behavior is essential for the functions of biomacromolecules such as proteins and peptides, including the formation of membraneless organelles and other supramolecular assemblies. Among them, there are two kinds of temperature-triggered phase separation behaviors existing in peptides/proteins, the lower critical solution temperature (LCST) of elastin-like peptides and the upper critical solution temperature (UCST) of resilin-like peptides. Especially, the UCST behavior of polymers is caused by the intrachain and interchain noncovalent interactions between themselves. As a UCST polymer, below the cloud point temperature ( T cp ), the polymer–polymer interaction is stronger than the polymer–water interaction, and hence two immiscible phases occur, a polymer-rich phase and a dilute phase of soluble polymer in water; when the temperature is higher than the clearing point temperature ( T cl ), the polymer–polymer interaction is disrupted, and the polymer forms a new interaction with water, and hence the polymer is miscible with water. Different from traditional polymers, the peptide chains with different sequences of amino acids as the primary structure are able to fold into different secondary structures, like α-helix and β-sheet .…”
Section: Introductionmentioning
confidence: 99%
“…9 Compared to UCST-type polymers, many studies have been reported on LCST-type polymers applied to the biomedical field, because they undergo a phase transition at physiological temperature and conditions, 10 which are less sensitive to pH and ionic strength. [11][12][13] Thanks to these advantages, LCST-type polymers have been actively studied. 12,14 Experimental characterization of such LCST phenomena has been studied using various measurement methods, including cloud point measurements, 15 dynamic light scattering, 16 and differential scanning calorimetry.…”
Section: Introductionmentioning
confidence: 99%